2006
DOI: 10.1097/01.rlu.0000246820.14892.d2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Primary Brain Tumors With FLT-PET: Usefulness and Limitations

Abstract: FLT-PET can be used to evaluate the malignant grade and proliferation activity of primary brain tumors, especially malignant brain tumors. However, the presence of benign lesions showing blood-brain barrier disruption cannot be distinguished from malignant tumors and needs to be carefully evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 13 publications
0
58
0
3
Order By: Relevance
“…Another study on 18 F-FLT PET uptake in recurrent malignant gliomas after bevacizumab treatment also showed that decreased 18 F-FLT uptake was associated with longer progression-free survival, although the evaluation of overall survival correlated better with 18 F-fluoro-L-phenylalanine (35). However, because of relatively low uptake of 18 F-FLT in brain tumors, disruption of the blood-brain barrier may interfere with proper evaluation of the tumors, since 18 F-FLT can be retained in some areas after successful therapy or in benign lesions as well (36). In addition to tumor SUVs, the use of combined 18 F-FLT kinetic changes has also been suggested for more accurately predicting treatment response, recurrence, and treatment outcome, since these take into account tracer delivery (37,38).…”
Section: Central Nervous System Cancersmentioning
confidence: 99%
“…Another study on 18 F-FLT PET uptake in recurrent malignant gliomas after bevacizumab treatment also showed that decreased 18 F-FLT uptake was associated with longer progression-free survival, although the evaluation of overall survival correlated better with 18 F-fluoro-L-phenylalanine (35). However, because of relatively low uptake of 18 F-FLT in brain tumors, disruption of the blood-brain barrier may interfere with proper evaluation of the tumors, since 18 F-FLT can be retained in some areas after successful therapy or in benign lesions as well (36). In addition to tumor SUVs, the use of combined 18 F-FLT kinetic changes has also been suggested for more accurately predicting treatment response, recurrence, and treatment outcome, since these take into account tracer delivery (37,38).…”
Section: Central Nervous System Cancersmentioning
confidence: 99%
“…Several studies have reported the utility of F-18 FLT in predicting the grade of gliomas. [3][4][5][6][7][8] Yamamoto et al in their study demonstrated significant correlation between metabolic volumes of recurrent glioblastoma multiforme and the volumes defined on MRI. 9 FLT was also better than methionine in tumor grading.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal brain, FLT is only slightly able to cross the intact BBB [31,32]. For this reason and because of the low proliferation of normal brain tissues, FLT has a very low background uptake in the brain and FLT is significantly taken up by HGG, which is associated with significant BBB breakdown [14][15][16][17]. But FLT is not significantly taken up in LGG because of the low TK1 activity and the relatively intact BBB (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…FLT PET, which can image tumor proliferation, seems to be suitable for evaluating the malignant grade of brain tumors and also for evaluating the treatment response. Although there have been few FLT studies for recurrent glioma, FLT may be feasible to use for detecting recurrent glioma because FLT has a high level of tumor-to-brain contrast in high-grade glioma that is associated with high thymidine kinase 1 (TK1) activity and significant breakdown of the blood-brain barrier (BBB) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%